The Desired Role of Healthcare Provider in Guiding Older Patients with Distal Radius Fractures: A Qualitative Analysis - Huetteman, Helen E. (J Hand Surg Am, 2018)
PURPOSE: Understanding patient preferences for shared decision-making is valuable for surgeons to advance patient-centered care, particularly in cases where there is not a clearly superior treatment option, like distal radius fracture (DRF). Existing evidence presents conflicting views on the desired role of the provider among older patients when making medical decisions. We aimed to investigate the perceived versus desired role of the provider in older adult patients with DRF. METHODS: Thirty patients (≥62 years old) who had sustained a DRF within the past five years were recruited from the screening process of the Wrist and Radius Injury Surgical Trial at principal investigator’s site using purposive sampling. A trained member of the research team conducted interviews in a semi-structured format with the help of an interview guide. Findings were derived following the principles of grounded theory. RESULTS: Participants experienced varied levels of shared decision-making with the hand surgeon. Subjects’ perceived role of the surgeon did not always match their desired role. Most patients placed distinct trust in the recommendations of hand specialists regarding the technical aspects of the treatment. Nonetheless, respondents wanted to provide input when decisions pertained to outcomes or functionality. Many patients sought outside support from family or friends in the healthcare field, regardless of the outside source’s medical specialty. CONCLUSIONS: Despite conflicting evidence, most older adult patients desire a shared approach when making treatment decisions. Exchanging information and preferences on outcomes of each treatment option may be more important to the patient than detailing the specific technical aspects of their care.